Narrow row spacing and high plant population to short height castor genotypes in two cropping seasons - Soratto, Rogério Peres [UNESP]; Souza-Schlick, Genivaldo D. [UNESP]; Fernandes, Adalton M. [UNESP]; Zanotto, Maurício Dutra [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Elsevier B.V., 2012)
Castor plant (Ricinus communis L.) produces a very important oil for chemical and biofuel industries. However, doubts remain about what the best plant arrangement is to obtain the maximum yield of seeds and oil from short height castor genotypes cultivated in higher plant population. This study evaluated two castor genotypes (FCA-PB and IAC 2028) in 5 plant arrangements (row spacing x in-row spacing): 0.90 m x 0.44 m (traditional), 0.90 m x 0.20 m, 0.75 m x 0.24 m, 0.60 x 0.30 m, and 0.45 m x 0.40 m, in spring-summer and fall-winter cropping seasons in Botucatu, São Paulo State, southeastern Brazil. The traditional plant arrangement comprised an initial plant population of 25,000 plants ha(-1), while the others comprised 55,000 plants ha-1. The IAC 2028 genotype presented the greatest plant height, first raceme insertion height, basal stem diameter, number of fruits per raceme and 100 seed weight; however, seed yield and seed oil content were equal between genotypes. Wider stems and higher number of racemes per plant and fruits per raceme were observed with a 0.90 m x 0.44 m plant arrangement, but due to the lowest plant population (25,000 plants ha(-1)) in this plant arrangement, the higher values of the yield components mentioned above did not result in higher yield. The higher plant population (55,000 plants ha(-1)) by narrower row spacings (0.45 or 0.60 m) combination produced a higher castor seed yield. The effect of plant arrangement was more intense in the spring-summer cropping season. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Ricinus communis; Oilseed crop; Spatial plant distribution; Yield components; Oil content